Realities of and perspectives for languages in the globalised world: Can language teaching survive the inadequacies of policies implemented today at Leeds Beckett University? - Gamir, Saadia (Studies in Second Language Learning and Teaching, 2017)
Various newspaper articles report that British ministers, university representatives, exam chiefs and business bodies agree that foreign languages skills in primary, secondary and tertiary UK education are in crisis. Lower funding and policy changes have caused language skills deficiencies felt gravely in the business sectors. Funding and support initiatives pledged by policy makers appear to be election-driven, barely outliving newly elected governments. Others blame secondary school language curriculum for failing to inspire students to take up a language when they reach 13 or 14. Others still argue that severe A-level examinations marking deters students from taking up a foreign language at 6th form level, producing fewer prospective language learners for university departments. Community languages are also undervalued as small-entry languages could soon be axed from GCSE and A-level examinations. In a world increasingly interconnected, it is essential the importance of language learning be reinstated in all our educational institutions. This paper reviews two decades of the conditions of language provision in the UK in general, with an emphasis on Leeds Beckett University. It also attempts to answer two questions emerging form the author’s personal teaching experience and reflections: What are the realities and challenges language teaching faces at Leeds Beckett University? And, how may we support language learners in fulfilling their ambition to acquire the required skills to communicate effectively in this globalised world?